Rapid and highly efficient morphogenic gene-mediated hexaploid wheat transformation - Johnson, Kari; Cao Chu, Uyen; Anthony, Geny; Wu, Emily; Che, Ping; Jones, Todd J. (Frontiers in Plant Science, 2023)
The successful employment of morphogenic regulator genes, Zm-Baby Boom (ZmBbm) and Zm-Wuschel2 (ZmWus2), for Agrobacterium-mediated transformation of maize (Zea mays L.) and sorghum (Sorghum bicolor L.) has been reported to improve transformation by inducing rapid somatic embryo formation. Here, we report two morphogenic gene-mediated wheat transformation methods, either with or without morphogenic and marker gene excision. These methods yield independent-transformation efficiency up to 58% and 75%, respectively. In both cases, the tissue culture duration for generating transgenic plants was significantly reduced from 80 to nearly 50 days. In addition, the transformation process was significantly simplified to make the procedure less labor-intensive, higher-throughput, and more cost-effective by eliminating the requirement for embryonic axis excision, bypassing the necessity for prolonged dual-selection steps for callus formation, and obviating the prerequisite of cytokinin for shoot regeneration. Furthermore, we have demonstrated the flexibility of the methods and generated high-quality transgenic events across multiple genotypes using herbicide (phosphinothricin, ethametsulfuron)- and antibiotic (G418)-based selections.